SOCIO-PSYCHOLOGICAL FEATURES OF THE FORMATION OF THE MODERN STUDENT FAMILY - Vovk М.В. (Pedagogy of Higher and Secondary Education, 2022)
In article are stated particularities to student family; her (its) specific problems and difficulties.